Love Wave Dispersion Analysis from Ambient Seismic Noise in Banyumas Basin, Central Java, Indonesia. Issue 1 (1st July 2022) - Kusuma, A H; Zulfakriza,; Nugraha, A D; Rosalia, S; Setiawan, A; Marjiono,
Abstract: The Banyumas Basin is one of a sedimentary basins in the southern coast of Central Java that has many manifestations of the presence of hydrocarbons in the form of oil and gas seeps found on the surface. Its presence is covered by a thick subvulcanic sedimentary layer. A conventional seismic active method which is usually used to delineate subsurface structures in an hydrocarbon area, however it can be challenging to imaged the structures beneath surface in areas covered by thick sub-volcanic sediments. Another method is needed to investigate the subsurface image in a thick sub-volcanic area, such as Banyumas basin. We cross correlated of the ambient seismic noise at transversal component to retrieve the love wave empirical Green's function. We used 40 broad band seismic stations for 60 days recording from Center for Geological Survey - Indonesian Geological Agency. The daily cross-correlated data then stacked to obtain the Love waves Green's function. The Green's function is clearly seen in 1-10 s period band. Then, the obtained Green's function will be analyzed to get the Love waves group velocity.